Beyond Compliance: How Does Internal CSR Drive Organizational Commitment in Nepalese Life Insurance Sector? - Chaudhary, Manoj Kumar; Neupane, Krishna; G.C., Suraj (Journal of Emerging Management Studies, 2025)
Purpose - This study examines the relationship between internal corporate social responsibility (iCSR) practices and organizational commitment, with a focus on the mediating role of job satisfaction. Specifically, it investigates how labor relations, work-life balance, health and safety, and training and development influence employee commitment. Design/methodology/approach – A quantitative research design was employed, using survey data collected from 243 employees of Nepalese Life Insurance Companies. The hypotheses were examined through regression models and correlation analysis. Moreover, mediation analysis was performed in SPSS using Hayes’ PROCESS macro with bootstrap resampling. Findings – The results reveal that work-life balance, health and safety, and training and development significantly enhance organizational commitment, both directly and indirectly through job satisfaction (partial mediation). Labor relations showed no significant impact, suggesting a shift in employee priorities toward well-being and growth over traditional labor policies. Conclusion – Internal CSR initiatives are crucial for fostering employee commitment, but their effectiveness varies across components. Job satisfaction partially mediates this relationship, indicating that additional psychological mechanisms may also be at play. Implications – Life Insurance Companies should prioritize work-life balance and training programs to maximize employee commitment. The non-significant effect of labor relations calls for a reevaluation of traditional HR practices to align with modern workforce expectations. Originality/value - This study contributes to CSR literature by empirically testing the differential impacts of internal CSR components, identifying job satisfaction as a partial mediator, and challenging conventional assumptions about labor relations’ role in commitment.